Assessing the long-term effects of zero-tillage on the macroporosity of Brazilian soils using X-ray Computed Tomography - Galdos, M.; Pires, L. F.; Cooper, H.; Calonego, J. C. [UNESP]; Rosolem, C. A. [UNESP]; Mooney, S. J. (Elsevier B.V., 2019)
Zero-tillage (ZT) is being increasingly adopted globally as a conservationist management system due to the environmental and agronomic benefits it provides. However, there remains little information on the tillage effect on soil pore characteristics such as shape, size and distribution, which in turn affect soil physical, chemical and biological processes. X-ray micro Computed Tomography (mu CT) facilitates a non-destructive method to assess soil structural properties in three-dimensions. We used X-ray mu CT at a resolution of 70 mu m to assess and calculate the shape, size and connectivity of the pore network in undisturbed soil samples collected from a long-term experiment (similar to 30 years) under zero tillage (ZT) and conventional tillage (CT) systems in Botucatu, Southeastern Brazil. In both systems, a single, large pore (> 1000 mm(3)) typically contributed to a large proportion of macroporosity, 91% in CT and 97% in ZT. Macroporosity was higher in ZT (19.7%) compared to CT (14.3%). However the average number of pores was almost twice in CT than ZT. The largest contribution in both treatments was from very complex shaped pores, followed by triaxial and acircular shaped. Pore connectivity analysis indicated that the soil under ZT was more connected that the soil under CT. Soil under CT had larger values of tortuosity than ZT in line with the connectivity results. The results from this study indicate that long-term adoption of ZT leads to higher macroporosity and connectivity of pores which is likely to have positive implications for nutrient cycling, root growth, soil gas fluxes and water dynamics.
Keywords: Zero tillage; Macroporosity; Pore connectivity; Network tortuosity; Pore shape